MoSx surface-modified, hybrid core-shell structured LiFePO4 cathode for superior Li-ion battery applications - Hu, Lung-Hao; Kumar, Pushpendra (Journal of Alloys and Compounds, 2021)
A hybrid core-shell cathode, composed of MoSx shell and carbon-coated lithium iron phosphate core (MoSx@cLiFePO(4) or MoSx@c-LFP) is obtained by the post-annealing of a thermally decomposable ammonium thiomolybdate and commercial carbon-coated LiFePO4 (c-LFP) powder. The specific capacity of the commercially available amorphous carbon-coated LFP (c-LFP) is typically around 120-160 mAhg(-1), which is usually lower than the theoretical values similar to 170 mAhg(-1) due to the limited Li+ phase-boundary diffusion and low electrical conductivity. In the present investigation, we report that the specific capacity of surfacemodified (similar to 1.2 wt% of layered MoSx) c-LFP (MoSx@c-LFP) material can reach as high as similar to 228 mAhg(-1) delivering high gravimetric energy density similar to 750-770 Whkg(-1). The excess capacity can be attributed to the partial Li-ions intercalated/de-intercalated through the MoSx layers within a specific potential range (2.0-3.8 V). MoSx coating helps increase the c-LFP surface's stability by forming strong covalent bonding and is believed to enhance the electronic conduction by reducing the interparticle contact. During charge and discharge the hysteresis is substantially reduced by MoSx coating. The approach may open up a universal route to increase the cathode capacity, potentially attractive for further Li-ion battery research and industrial applications. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Ammonium thiomolybdate; Coulombic efficiency; Hybrid core-shell cathode; hysteresis; MoSx